2011
DOI: 10.17925/ohr.2011.07.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Nausea and Vomiting During Chemotherapy

Abstract: Nausea and vomiting are two of the most troubling side effects patients experience during chemotherapy. While newly available treatments have improved our ability to manage nausea and vomiting, anticipatory and delayed nausea and vomiting are still a major problem for patients receiving chemotherapy. Many cancer patients will delay or refuse future chemotherapy treatments and contemplate stopping chemotherapy altogether because of their fear of experiencing further nausea and vomiting. The purpose of this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 104 publications
2
28
0
1
Order By: Relevance
“…94,95 Adherence to these guidelines improves control of CINV by approximately 20%. 96 Chemotherapy regimens are classified into four categories according to potential for CINV—highly emetogenic (>90%), moderately emetogenic (both with and without anthracycline and cyclophosphamide [AC]; 30–90%), low emetogenic (10–30%), and minimally emetogenic (<10%).…”
Section: Clinical Guidelinesmentioning
confidence: 99%
“…94,95 Adherence to these guidelines improves control of CINV by approximately 20%. 96 Chemotherapy regimens are classified into four categories according to potential for CINV—highly emetogenic (>90%), moderately emetogenic (both with and without anthracycline and cyclophosphamide [AC]; 30–90%), low emetogenic (10–30%), and minimally emetogenic (<10%).…”
Section: Clinical Guidelinesmentioning
confidence: 99%
“…These interventions include behavioral, non-pharmacologic, and other supportive measures intended to decrease the effect of nausea on children with cancer. [99][100][101][102][103] The findings of this study also support the need for a dynamic collection process of HRQOL in children undergoing curative cancer treatments. Our study identified the longitudinal nature of HRQOL outcomes over time in children with cancer.…”
Section: Practice Implicationssupporting
confidence: 62%
“…Beyond recommending the appropriate use of myeloid growth factor and infection prophylaxis, pharmacists play an important role in preventing and managing chemotherapy-induced nausea and vomiting (CINV). CINV occurs in up to 80% of patients on active therapy and remains a significant barrier to quality of life [12]. When uncontrolled, CINV can alter electrolytes and enteral nutrition, leading to detrimental effects on patient adherence and health outcomes [13].…”
Section: Infection Prevention and Supportive Carementioning
confidence: 99%